2020
DOI: 10.1002/pbc.28606
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response effect of eribulin in preclinical models of osteosarcoma by the pediatric preclinical testing consortium

Abstract: The pediatric preclinical testing program previously demonstrated activity of eribulin in osteosarcoma patient‐derived xenograft (PDX) models. The phase 2 trial in patients with relapsed osteosarcoma failed to meet response endpoints. Eribulin was evaluated in the original and an expanded set of PDX models and tested at multiple dose levels and schedules to evaluate dose‐response. Maximal response was observed at the highest dose, consistent with prior results. The alternative schedule generated similar respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…It inhibits microtubule growth 60) and blocks the cell cycle at the G2-M phase 61,62) . Preclinical studies using patient-derived xenografts (PDX) for relapsed OS have been reported in several groups 63,64) , which is consistent with our results. In contrast, stronger anti-proliferative effects of ifosfamide and dagarbazine were detected in ESOS than in OS.…”
Section: Discussionsupporting
confidence: 92%
“…It inhibits microtubule growth 60) and blocks the cell cycle at the G2-M phase 61,62) . Preclinical studies using patient-derived xenografts (PDX) for relapsed OS have been reported in several groups 63,64) , which is consistent with our results. In contrast, stronger anti-proliferative effects of ifosfamide and dagarbazine were detected in ESOS than in OS.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to their steep dose response curve suggesting that activity may drop significantly below the threshold concentration/exposure. This was seen in osteosarcoma whereby significant responses were seen in PDX models but none were observed in the phase 2 trial in patients with recurrent osteosarcoma [100,104,105]. Ultimately the recommendation of the task force was to await the results from the ongoing trials prior to designing a new clinical trial for RMS.…”
Section: Novel Cytotoxic Agents: Eribulinmentioning
confidence: 99%
“…This agent demonstrated a robust signal of efficacy in the murine model, 41 but the resulting phase II clinical trial failed to meet its efficacy threshold 42 . This negative trial led to re‐examination of eribulin in the original PDX models and multiple additional PDX models, again demonstrating excellent efficacy in murine models 43 . The authors demonstrate a steep dose–response curve for eribulin in PDX models, underscoring the importance of robust pharmacokinetic and pharmacodynamic assessments in both the preclinical and clinical settings to ensure effective concentrations are achieved 43 .…”
Section: Challengesmentioning
confidence: 99%
“…This negative trial led to re‐examination of eribulin in the original PDX models and multiple additional PDX models, again demonstrating excellent efficacy in murine models 43 . The authors demonstrate a steep dose–response curve for eribulin in PDX models, underscoring the importance of robust pharmacokinetic and pharmacodynamic assessments in both the preclinical and clinical settings to ensure effective concentrations are achieved 43 . Emerging evidence also suggests that the activity of eribulin may be in early metastasis development, a mechanism that may not be adequately evaluated in current study designs aimed at testing agents in the setting of relapsed disease 44,45 …”
Section: Challengesmentioning
confidence: 99%